Analysis of Criminal Investigation of Sexual Abuse Against Mentally Disabled Children at the Aceh Tengah Police Department - Khairul Huda Rizka; Fitri Rafianti; Mhd. Azhali Siregar (PT. Sinergi Legal Publisher, 2025)
This study aims to analyze the investigation process of child molestation crimes against children with mental retardation at the Central Aceh Police, as well as to identify inhibiting factors and efforts to overcome obstacles in its implementation. This study uses an empirical juridical approach with a focus on the effectiveness of the implementation of laws and regulations, such as Law Number 8 of 1981 concerning Criminal Procedure, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, Law Number 35 of 2014 concerning Child Protection, and Law Number 8 of 2016 concerning Persons with Disabilities. The results of the study indicate that investigations of child victims with intellectual disabilities still face various structural, technical, and cultural obstacles, including limited technical regulations, a lack of investigator competence in an inclusive approach, and the absence of supporting facilities. This leads to a distortion of justice that deviates from the principle of due process of law and the substance of juvenile justice. Within the framework of responsive legal theory and corrective justice, it is concluded that reform of investigative procedures for children with special needs is a legal and ethical necessity. Investigations must be based not only on the objective of formal evidence, but also on the imperative of protecting and respecting human dignity. Therefore, the state is required to be a real, impartial protector, not merely an enforcer of procedures.